O Projeto Rawlsiano de justiça social para a sociedade dos povos - Zeifert, Anna Paula Bagetti (2018)
In this thesis we analyze the elements that involve the theory of social justice in Rawls, covering the three main works of the author - Theory of Justice, Political Liberalism and The Law of Peoples - with the aim of identifying, from the beginning, a social ideal social ideal), with a view to a full conception of justice. As a basis for the development of the research, the fundamental elements - basic structure and just social institutions, principles of justice and the idea of cooperation - that guide the conception of justice in Rawls, first for national societies and later in defense of a Peoples' Society. We have shown that throughout Rawlsian theory, implicitly or explicitly, both in national societies and in the Peoples' Society, a social ideal has always been present as a project for a full conception of justice. However, we note that The Law of Peoples's proposed social justice system faced even greater challenges because of pluralism and the need to architect a parallel process of justice (national and international). In the thesis, we argue that the social ideal that permeated the discussions at the national level was extended to the Peoples' Society as a way of promoting justice among peoples and bringing together societies that are in an unfavorable (burdened) situation. The Duty of Assistance, a principle built to govern relations between peoples, is the new element introduced by Rawls to guarantee and make feasible his social ideal within the framework of international society. We consider that this social ideal is anchored in the notion of basic structure and in the benefit of social cooperation, fundamental ideas of Rawlsian thought since A Theory. We argue that the idea of assistance among peoples does not pretend to be a global distributive justice project based on the principle of difference for national societies, but that the Duty of Assistance is the expression of the Rawlsian social ideal, now extended to Society of Peoples.